Sensitivity and Specificity of Nested PCR for Diagnosing Malaria: Cases in Several Areas of Indonesia - Arifin, Samsul; Fitri, Loeki Enggar; Sujuti, Hidayat; Hermansyah, Bagus; Endharti, Agustina Tri; Burhan, Niniek; Candradikusuma, Didi; Sulistyaningsih, Erma; Tuda, Josef Sem Berth; Zein, Umar (Journal of Tropical Life Science, 2018)
Indonesia is still included in high endemic area of malaria infection. Early detection as well as appropriate and quick treatment is needed to be able to prevent and treat malaria in Indonesia. Laboratory examination using a microscopic method is still used as the gold standard to diagnose malaria cases. However, the morphology similarity of some Plasmodium species and the number of parasites that can be seen under microscopy causes malaria diagnosis become difficult if only relying on microscopy diagnostic method. The purpose of this study is to analyze the sensitivity and specificity of nested PCR compared to microscopic examination in diagnosing malaria cases. A cross-sectional study has been carried out in some areas of Indonesia and the microscopic analysis as well as nest PCR was done in Laboratory of Parasitology and Laboratory of Central Biomedical Faculty of Medicine, Universitas Brawijaya, Malang East Java Indonesia. A total of 149 blood samples from patients with clinical symptoms of malaria had been obtained from Sumatra, Sulawesi and East Java during December 2011 to December 2013. From 149 sample, 81.9% samples were diagnosed malaria positive by microscopy examination, whereas the PCR results showed that 90.6% of samples were positive. Nested PCR sensitivity is 97.5%, and microscopy 88.2%. Nested PCR specificity is 40.7%, whereas microscopy 78.5%. PPV and NPV for nested PCR are 88,2% and 78.5% respectively, and for microscopy are 97.5% and 40.7% respectively. Nested PCR has a higher sensitivity than microscopy in diagnosing malaria and is able to detect mixed infection better than microscopic examination. However, it is statistically less specific than microscopy examination.